Experimental measurement-device-independent quantum digital signatures - G. L. Roberts (Nature Portfolio, 2017)
Measurement-device-independent quantum digital signatures would allow a document to be signed and transferred with information-theoretic security. Here, the authors reach this goal using a reconfigurable quantum network where the central node can switch between trusted and untrusted operation.